The Influence of Emotional Intelligence, Intellectual Intelligence and Spiritual Intelligence on the Member Performance in Mamuju Regency - Muh Said; Mustaking Mustaking (Universitas Negeri Makassar, 2021)
spiritual intelligence on the performance of members of the Regional House of Representatives of Mamuju Regency. This research was conducted at the office of the Regional House of Representatives, Mamuju Regency, West Sulawesi. by taking 30 members of the Regional House of Representatives as the research sample. The results of this study prove that partially proven emotional intelligence, intellectual intelligence, and spiritual intelligence, have a positive and significant effect on the performance of members of the Regional People's Representative Council. This study also proves that simultaneously emotional intelligence, intellectual intelligence, and spiritual intelligence have an effect on the performance of members of the Regional Representatives Council of Mamuju Regency. This study resulted in a coefficient of determination of 61.8% which indicates that this research model can explain that the performance of members of the Regional House of Representatives of Mamuju Regency is influenced by 61.8% of this research variable and 38.2% is influenced by other variables not examined. in this research.